2005
DOI: 10.1007/s10867-005-2043-1
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Different-Scale Membrane Processes Under Nitric Oxide Influence

Abstract: Rhythmic activity, synaptic transmission and propagation of excitation depend on the processes that occur at different cellular levels. Modulation of neuron activity results from the changes of plasma membrane and organelles properties. We aimed to study the relationship between changes of the ion channels activity, membrane microviscosity and amount of bound Ca(2+) under the influence of nitric oxide (NO). We also investigated the effect of NO on the refractive index of neurons. We have shown that NO activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 41 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…We have studied the intracellular dynamics in a broader frequency region and have shown that different types of neurons, erythrocytes and mast cells display regular changes in RI with frequencies in the 0.1-30 Hz range that are specific for each cell type (Sosnovtseva et al 2005;Brazhe et al 2005Brazhe et al , 2006. However, even if the best approaches to interference microscopy are applied, a significant amount of valuable information about the cell compartmentalization and dynamics may remain undetected.…”
Section: Introductionmentioning
confidence: 99%
“…We have studied the intracellular dynamics in a broader frequency region and have shown that different types of neurons, erythrocytes and mast cells display regular changes in RI with frequencies in the 0.1-30 Hz range that are specific for each cell type (Sosnovtseva et al 2005;Brazhe et al 2005Brazhe et al , 2006. However, even if the best approaches to interference microscopy are applied, a significant amount of valuable information about the cell compartmentalization and dynamics may remain undetected.…”
Section: Introductionmentioning
confidence: 99%